Peran Sekolah Ekspor dalam Mencetak Eksportir Baru melalui Program Studi Independen Be a Digital Exporter - Apriliana Ervynasari; Sitti Retno Faridatussalam (Yayasan Literasi Sains Indonesia, 2025)
The number of active exporters in Indonesia remains low compared to the country’s vast national resource potential, particularly in the MSME sector. Low export literacy, complex regulations, and limited access to global markets are the main challenges. The Independent Study Program “Be a Digital Exporter” by Sekolah Ekspor offers a strategic solution through vocational and digital-based education. This study employs a descriptive qualitative method using participatory observation and questionnaires targeting participants of the 7th batch. The findings indicate that the program successfully enhanced participants’ understanding and export skills through practical learning based on the 7 in 1 Arrows of Export Management framework. Challenges such as miscommunication, technical difficulties, and heavy workloads were addressed through system adjustments, mentoring, and curriculum improvements. The program has proven to contribute significantly to participants’ readiness to become adaptive beginner exporters in global markets. Furthermore, collaboration with local MSMEs and the use of digital technology strengthen the competitiveness of Indonesian products. This study recommends enhancing mentor communication systems, expanding access to technology, and implementing continuous evaluation to support the acceleration of producing 500,000 new exporters by 2030.